The Scientific American book of love, sex, and the brain the neuroscience of how, when, why, and who we love - Horstman, Judith (Scientific American brain series, 2012)
"A fascinating look at how the brain controls our relationships and romances. Neuroscientists, psychologists, and most men and women readers today have learned that the brain is Grand Central Station for our most erotic associations, memories, and secret desires. The latest research shows that the popular myth is true: Sexual orientation and identity is hard-wired, the result of our neurological predisposition, not a choice or result of socialization. We instinctively crave connection and relationship as an essential part of our well-being, self-esteem, and pleasure. The process of achieving and recovering from orgasm ignites the same pleasure centers in the brain as exercise, music, religion, food, alcohol, and drugs. Sexual desire can be triggered by a thought, a smell, a touch, or the sight of an object of desire. These sensorium are located at different parts of the brain, and can be activated indefinitely into our senior years. Filled with little known and fascinating information about the brain. The third Scientific American book in the series about the brain. The core science and latest research is drawn from the prestigious Scientific American and Scientific American Mind magazines"--